Genotoxicidade e citotoxicidade de corantes azóicos em ensaio do micronúcleo in vivo (Swiss albinus) - SOUZA, Carolina C. S. H. (2015)
The addition of the food coloring plays an important role in the food industry under the technological point of view. Natural dyes are difficult to navigate in standard products, so we were created synthetic dyes. Among artificial synthetic dyes allowed by law, are those of azo group and its use is one of the most controversial developments in the sector. The use of these substances is still raising a lot of questions as to toxicity, because in the literature, working with this momentum is limited and controversial. In this context, the aim, with this study was to evaluate the genotoxic potential of azo dyes by the micronucleus assay (MN). The MN test is widely used and internationally accepted for evaluation of mutagenic actions. The in vivo genotoxicity test was applied to research observed in erythrocytes Polychromatic (PCE) extracted from the bone marrow of the femur 168 Swiss mice Albinus, male and female, underwent five treatments (N-nitroso-N-ethylurea: control+; 150 mM NaCl: Control–; dye at 1, 1.5 and 2 g.Kg-1) and used four azo dyes (Tartrazine, Sunset Yellow, Red 40, Ponceau 4R) for 24h and 48h (after this time euthanasia was performed). We analyzed also the PCE/NCE ratio, which it is an important marker of cytotoxicity. The data obtained in the MN assay were subjected to analysis of one-way variance (ANOVA) using a factorial scheme of 5 × 2 × 2 (treatment × sex × time), and average compared to Tukey's test (p < 0.05) using SAS® software version 9.3. The dye Tartrazine showed genotoxicity dose- and sex-dependent; Sunset Yellow was genotoxic sex-independent; Red 40, its genotoxicity was dependent on the exposure time and the sex of the animal; the dye Ponceau 4R genotoxicity depends on the dose and time until euthanasia. However, it can be concluded that studies of these food additives often must be performed in order to constantly update data that are safe for consumption, since all four dyes tested in this study showed some degree of toxicity. Recalling that they have the use regulated by specific legislation establishing the Maximum Allowable Limits (LMP) and patterns of Acceptable Daily Intake for humans, extrapolated to animals. However, despite the control required by regulatory agencies, the use of dyes in food continues to raise a number of questions, mainly due to lack of studies evaluating the toxicity of these compounds which reinforces the attention they should be given.